Tinjauan Fikih Muamalah atas Transaksi pada Aplikasi Grab Food - Muhajir, Muhajir (Program Studi Hukum Ekonomi Syariah, 2023)
The development of increasingly advanced technology has made muamalah transactions easier through online transactions, in this case Grab provides a food delivery service, namely Grab Food which can be accessed by Grab Food application users. Customers can use food delivery services according to their interests. When Grab drivers receive orders from customers for food ordering services, the driver will provide customer funds first which will then be reimbursed by the buyer after the order reaches the buyer. But in this case, it is not only the driver and the buyer who are involved in this transaction. There are still food sellers and PT Grab as service providers. This indirectly occurs the merger of contracts which are collected into three contracts, namely: salam contract, ijarah and wakalah. Fiqh scholars give different legal statuses to this double or multi-contract contract because the status of one contract is not necessarily the same as the status of the contract that built it. For this reason, the author is interested in further researching the contracts that occur in the Grab Food application, the focus of this research is on the validity of transactions on the Grab Food application reviewed from the fiqh muamalah. The method used in this study is field research. The technical data analysis used is qualitative descriptive analysis. The data sources used in this study are primary data sources through interviews obtained directly from PT Grab branch of Purworejo, drivers, food sellers and food buyers, and secondary data sources obtained from books, journal articles, and news from the internet related to this study. The results of this paper conclude that the contracts collected when transacting on the Grab Food application are in accordance with the terms and principles of the contract in the fiqh muamalah and multi-contract in this transaction is permissible.